Small-Cracked Concretes Based On Aral Sand Using Secondary Crushed Crushed Concrete - Assistant Z.J. Pasieva; Docent. Sh.M. Davlyatov (Peerian Journals Publishing, 2025)
The article shows that for regions experiencing a shortage of large aggregates, it is possible to use low-gravel concrete with an increased sand content. Compounds with sand content, characteristic of low-gravel concretes with the lowest structural viscosity, were isolated. For these compositions, with the same compaction time using vibration, the requirements for the workability of low-gravel concrete can be reduced several times. This is due to the fact that the ability of crushed stone concrete mix to liquefy during vibration compaction is higher. Consequently, concrete mixtures fill the formwork better in a shorter time, i.e., they have increased forming ability, which allows for the use of harder concrete mixtures with reduced cement and water consumption. The study of the flow process of low-gravel concrete mixtures through a calibrated opening during vibration showed that the flow time of uniformly moving (with the same settlement of the standard cone) mixtures is reduced several times. The use of more rigid low-gravel concrete mixtures leads not only to a decrease in water and cement, but also to an increase in crack resistance, frost resistance, strength, and water resistance. Thus, it has been established that using low-gravel mixtures instead of conventional concrete mixtures contributes to increased efficiency, as it leads to a decrease in material and energy resources.
Keywords: small-gravel concretes; structure; formability